Into the thaw : witnessing wonder amid the Arctic climate crisis - Waterman, Jonathan (Patagonia Books, 2024)
Forty years ago, the park ranger Jon Waterman took his first journey into the Alaskan Arctic, to the Noatak headwaters. He was astonished by the abundant wildlife, the strange landscape, and its otherworldly light--how the "frequent rain showers glow like lemonade poured out of the sky." Taken with a new sense of wonder, he began to explore the North on several trips in the 1980s. After a 30-year absence from the Noatak, he returned with his son in 2021. Amid a now-flooded river missing the once-plentiful caribou, he was shocked and heartbroken by the changes. The following year, in 2022, he took one final journey "into the thaw" to document--for this lushly illustrated and scholarly book--the environmental and cultural changes wrought by the climate crisis.